Diagnosis and Treatment of Intraoperative Popliteus Tendon Impingement - Kazakin, Anatoly; Nandi, Sumon; Bono, James (The Journal of Knee Surgery, 2014)
Herein, we describe a simple, effective strategy for diagnosing and treating intraoperative popliteus tendon impingement during total knee arthroplasty (TKA). When lateral impingement is detected intraoperatively during TKA, manual isolation of the popliteus tendon can help determine the cause. Using this technique, the etiology of intraoperative lateral impingement during TKA was never misdiagnosed and the popliteus tendon was never unnecessarily released. The technique described allows for accurate diagnosis of intraoperative lateral impingement during TKA and the prevention of unnecessary popliteus resection.
Keywords: popliteus; total knee arthroplasty; knee; impingement; technique